İtikadi açıdan zikir kavramı - Yaman, Vezire (My University, 2010)
Allah’a ibadet etmek için yaratılan insanın temel görevlerinden biri de O’nu anmak, hatırlamak, unutmamak anlamlarına gelen zikirdir. Sözlükte; “anmak, hatırlamak, unutmamak, bir işte bulunan düzen söz, kitap, öğüt, nasihat, uyarı, ikaz” anlamlarına gelen zikir, terim olarak; “Allah’ı unutmayıp daima hatırında tutma; O’nun isimlerini anıp duâ ve niyazda bulunma” şeklinde tanımlanamaktadır. Zikir kavramı Kur’ân-ı Kerîm’in çeşitli âyetlerinde tekrarlanmakta, bunların büyük çoğunluğu doğrudan zât-ı ilâhiyyeye, O’nun ismine ve rab kelimesine nisbet edilmektedir. Zikir mecazen şan-şeref ve Kur’ân mânalarında da kullanılmaktadır. Zikir kavramı birçok hadis rivâyetinde benzer muhtevada yer almaktadır. Zikrin asıl mânası kâinatı yaratan ve idare eden en yüce varlığı hatırdan çıkarmamaktır. Bu bezm-i elest’te O’nunla yaptığımız anlaşmanın ve ilâhî emaneti taşımayı kabul eden insana özgü selim fıtratın bir gereğidir. Bununla birlikte zikir üçe ayrılır. 1- Dil ile zikir. 2- Kalp ile zikir. 3- Bedenle zikir. Dil ile zikir; tevhîd inancını dile getiren, pekiştiren, Allah’ı yücelten, O’nun zatına yakışmayan şeyleri O’ndan uzaklaştırmak için kullanılan kelime ve cümleleri dil ile söylemek demektir. Bu amaçla “Allah’ın güzel isimleri” anlamına gelen esmâ-i hüüsnâ en çok başvurulan kelimelerdir. Bunun yanında duâ etmek, namaz da okunan duâlar dil ile zikir kavramı içinde yer alır. Kalp ile zikir ise; esas olan zikir türüdür. Zihninde katılmasıyla istenilen zikir türü budur. Bedenle zikir ise; Allah’ın insana emanet olarak verdiği bedeni O’nun emir ve yasaklarına uygun olarak kullanmasıdır. Namaz kılmak, oruç tutmak gibi ibadetlerin yanında bedeni yaratılışına uygun kullanmakta bu kapsamın içindedir. İslâmî ilimler içinde zikirle ilgili en kapsamlı literatüre tasavvufta rastlamaktayız. Tasavvufta daha çok dil ile zikir öne çıkarılmıştır. İnsanın kulluk görevleri içinde yer alan zikir, Allah’ı anmak; Kur’ân’ın tabiriyle “Allah’ı zikretmektir.” Kur’ân’da bir çok âyette “Allah’ı zikredin” emri verilmiştir. Yüce Allah, “Siz Beni zikredin ki Ben de sizi zikredeyim” buyurmuştur. Âlimler ve zâhidler esmâ-i hüsnâ’yı veya İslâm’ın insanlığa haber verip rehberlik ettiği yüce varlığın hangi dille olursa olsun adını anarak zikretmeyi de tavsiye etmiştir. Dil ile olan bu zikir asıl olan kalbin (zihnin ve gönlün) zikrine ulaşmaya yardımcı olmaktadır. THE CONCEPT OF DHİKİR (REMEMBRANCE OF ALLAH) İNTERMS FAİTH

Created to worship God one of man’s fundamental mission to commemorate him, to remember, not forget the meaning is remembrance. İn the dictionary, to commemorate,to remember, do not forget,a job the order,books, advice, counsel, warning wich means remembrance, the term as, God then forget not always hold, then the name of henor and prayer and and supplication in the so defined. Being repeated invarious verses of the Qur’an, the concept of remembrance, majorits and the lerd God and His word in the name of-honor and glory proportion dhkir connetations are also used in the meaning of the Qur’an. The concept of dhikr in the hadith book’s contents are similar. Remembrance of the original meaning of the universe created and managed not to remave the most exalted existence elest bezm Him in this agreement and agree to bear the divine deposit wich is a requirement of human specific benign nature. However, with remembrance three parts, with the heart dhikr, the remembrance of the body expressed the belief that unity through language reinforce the remembrance of Allah and gloifying Him what the is not worthy of the person away is to say word and sentences with language. Beautiful names of Allah, which means for this purpose Esmâ-i hüsnâ are the most referenced words. I proy by proying with heart to language with in the concept of remembrance of the principles and desired participotion in his mind the remembrance of the God’s people entiusted to his body, His commandments and prohibitions in accordance with the namaz to render fasting, suchas worship, along side the body of creation accordion to uses of this scope İslâmî trends in remembrance about the most comprehensive Works boks and sufi literatüre come across. İn sufi dhikir with more languages have been put forword. One of the respon sibilities of people who worship God with the remembrance of Allah, the Qur’ân expression dhikir. Qur’ân the most mentioned orders are given. I mentioned to you that Allah has commanted I’ll men tion you. Esmâ-i hüsnâ, or İslamic scholars and zahid notice and quidance to humanity’s great assets that no matter what language it also recommend that the heart (the mind and heart)helps to achieve the remembrance. There is no doubt that prayer and reading the Qur’ân and dhikir in the heart of the most effective in terms of participation takes place at the begining of prayer. Carries a deep prayer of the prophet and petition has been . To numerous mention the book of Allah, wath Allah intended not to remember, to read the Qur’ân prayer, praying end begging God to be found and the name is simply to repeat. But it has less continuous remembrance of Allah always keep in mind, and soul, not to forget him unconscious, the remembrance is more voluoble than a disingenuous way instead of under stading the shope as a result of the Qur’ân and dhikir the command of circumcision down loads orders and expansion must be taken into account, the model shoud be adopted in these two sources. Dhikir is to narrow the meaning of certain patterns to reduce it. A remembrance of people away from the understanding of sociol life will not fit with İslamic principles.
Keywords: İslam Dini; Kelam